Analisis Geologi Daerah Gunung Pani, Kecamatan Buntulia, Kabupaten Pohuwato, Provinsi Gorontalo - Muhtar, Muhtar; Permana, Aang Panji; Kasim, Muh; Sosang, Agustinus (Journal of Applied Geoscience and Engineering, 2024)
The research location is situated in Mount Pani, Hulawa Village, Buntulia District, Pohuwato Regency, Gorontalo Province. The objective of this research is to determine the geology of the study area and analyze the hydrothermal alteration zones within the research area. The research methods used include surface geological surveys and petrography. The findings reveal that the geomorphological conditions of the research area are divided into one unit, namely a fault zone hill unit. The stratigraphy of the area consists of four units: tuff unit, porphyritic rhyodacite unit, banded rhyodacite unit, and rhyodacitic breccia unit (auto breccia). In terms of geological structures, there are joints in the form of shear joints, which are the result of compression stress, and tension joints. The fault structures in the study area include oblique faults, with the dominant directions being NE-SW and SE-NW. At station M044, a sinistral normal fault (normal left-slip fault) was found; at station M052, a dextral normal fault (normal right-slip fault); at station M079, a sinistral fault (left-slip fault); while fault breccia at stations M02, AL052, and AL29 is interpreted as a sinistral fault with a NE-SW direction.